Ein Beitrag zur Auslegung tragender Klebverbindungen im Fassadenbau - Bues, Martin Dirk (Berichte zum Stahl- und Leichtbau, 2022)
This work describes investigations into the design of load-bearing bonded joints facade construction. The core element is the analysis of the time- and temperature-dependent load-bearing behavior of bonded joints. For this purpose, actions are analyzed, the time- and temperature-dependent behavior of various adhesives is investigated experimentally and theoretical considerations of the load-bearing behavior are carried out.